Study on the acceptance of mobility management measures for people with disabilities - da Invenção, Deisiane Santos; Freire, Aline Carolina Prado; Pinto, Ilce Marília Dantas; Delgado, Juan Pedro Moreno; Miranda, Silvia Camargo Fernandes (Seven Editora, 2023)
The current work is a continuation of research developed in 2018, on the campus of the Federal University of Bahia (UFBA) with the participation of professionals from the transport and transit area, aiming to identify the degree of importance of the Mobility Management Measures presented (MGM). The justification for continuing the research was to hear the opinion of students with disabilities about the adequacy of the strategies chosen by the professionals because of the reality of UFBA to validate the strategies indicated in the first phase of the research. The analysis of the results indicated that all the GMMs identified by the specialists fit the reality of the university from the point of view of students with disabilities and that in addition to them, adjustments must be made to the architecture of UFBA to improve the accessibility of the PWD to this institution.DOI:https://doi.org/10.56238/alookdevelopv1-129